The quality of the first and second Vaal Triangle Airshed Priority Area (VTAPA) Air Quality Management Plans - Moreoane, Lehlogonolo; Mukwevho, Phathutshedzo; Burger, Roelof (Clean Air Journal, 2021)
In response to deteriorating air quality, South Africa implemented national programmes that aim to manage and regulate ambient air quality and air pollution. Air Quality Management Plans (AQMPs) are clear outlines of measures and resources needed to achieve air quality objectives in a given geographical area and require support from government, business, industry, non-governmental organisations (NGOs) and the public. The success of the AQMPs depends primarily on the support of all stakeholders and the quality of the management plan. The Vaal Triangle Airshed Priority Area (VTAPA) was declared in 2006 as an area where ambient air quality standards are exceeded or may cause adverse air quality impacts. This research study focused on the VTAPA to evaluate the quality of the first and second-generation AQMPs for the VTAPA. Quality evaluation includes an analysis of procedures, processes, methods and documents. Effectiveness refers to the results of individual activities; therefore, the extent to which the AQMP met the expected outcomes of the review package defined the quality of the AQMP report. Both the first and draft second-generation AQMPs were considered to be of good quality. The first-generation AQMP was found to be of better quality than that of the draft second-generation AQMP. Funding mechanisms need to be investigated to assist in implementing intervention strategies in the AQMP as both the first and draft second-generation AQMPs were found to lack the potential to secure funds. Though the draft second-generation AQMP was found to be of lesser quality, the source apportionment study for identification of all sources as well as a better-outlined air quality management system was found to be good improvements to the AQMP.